المحكات التشخيصية بالدليل التشخيصي والإحصائي DSM لتشخيص اضطراب طيف التوحد - عثمان، فاطمة محمد مصطفى (جامعة الزيتونة - كلية التربية - سوق الأحد, 2021)
The significant increase in the number of people with utism became a global issue that required intensified efforts and opportunities for scholarly and scientific discussions and meetings in order to understand and identify it. Autism spectrum disorder is one of the most difficult and complex developmental disorders due to the difficulty of diagnosing and identifying it as it overlaps with other developmental disorders that share many symptoms with it, which may result in having differences between specialists in determining the degree of damage and severity. This necessitated having diagnostic criteria to avoid confusion, and as a document that can be used easily. The diagnostic and statistical manual issued by the American Psychiatric Association provides several diagnostic tests that help build a clinical picture of the behavioral symptom shape, to determine the degree and severity of autism, as well as the degree of support and other details related to its relationship to some other disorders and disabilities. It defines it as a differential diagnosis that includes a diagnosis of autism as an independent category with specific symptoms that range from mild to moderate too severe. Thus, the present study seeks to refer to the diagnostic criteria that facilitate the process of diagnosis, as well as the measures that can be used to achieve the same goal.
Keywords: الاضطرابات النفسية -- طيف التوحد -- المعايير التشخيصية